Nursing Informatics Truths, Talent, and Transforming the Future. - Carroll, Whende M. (Oxford : Productivity Press, 2024)
This book will explicitly detail why, how, and where nurses can utilize their much-needed abilities to evolve their nursing careers and move health IT into the future.
4.2 What Nurse Informaticists Naturally Encompass -- Cornerstones of Nursing: Care, Compassion, and Empathy
Description based upon print version of record.
Keywords: MEDICAL / Nursing / Management & Leadership; Nursing informatics